FUNCTIONAL GRAMMAR STUDY: ANALYZING THE BATAK PROVERB "DALIHAN NATOLU" FROM THE PERSPECTIVE OF SYSTEMIC FUNCTIONAL GRAMMAR - Rahmawati Rahmawati; Arwin Tannuary; Herman Herman; Arisdani Elman Situmorang; Yuni Enjelina Napitupulu; Dewi Kristina Hutapea; Silvia Sherina Pangaribuan; Elina Rosa Sihotang (Indonesian EFL Journal, 2025)
Proverbs that represent their values and perspective are part of the rich cultural legacy of the Batak people of North Sumatra, Indonesia. "Dalihan Natolu" (translates as "The Three Hearth Stones") is one such proverb. This proverb is an important part of Batak social structure and values, which makes it a valuable topic for linguistic study. The "Dalihan Natolu" proverb is examined in this study using the Systemic Functional Grammar (SFG) theoretical paradigm. SFG is a linguistic approach that examines the ways in which language is employed to create meaning and depict the outside world. We can learn more about the grammatical and semantic elements of the "Dalihan Natolu" proverb that contribute to its cultural importance by using SFG to analyze it. The ideational, interpersonal, and textual meta functions of SFG are the three main areas of analysis. The proverb's representation of experiences and construction of reality are examined by the ideational meta function. The interpersonal meta function looks at how the proverb conveys the speaker's position and enacts social interactions. The textual meta function looks at the proverb's method of arranging ideas to create a logical and cohesive message. The study's goal is to identify the language structures and patterns that underlie the cultural significance and symbolic force of the "Dalihan Natolu" adage through this in-depth investigation. Understanding the proverb from the standpoint of Systemic Functional Grammar helps us to better grasp the richness and complexity of Batak cultural expression as well as its applicability in the contemporary era. The results of this work advance the field of linguistic analysis of cultural artefacts and the academic understanding of Batak language and culture. In light of the swift advancements in social and technological spheres, the knowledge acquired can also contribute to the preservation and promotion of Batak cultural heritage.